The role of tropical small-scale fisheries in trace element delivery for a Small Island Developing State community, the Seychelles. (August 2022) - Sabino, Magali A.; Bodin, Nathalie; Govinden, Rodney; Arrisol, Rona; Churlaud, Carine; Pethybridge, Heidi; Bustamante, Paco
Abstract: The concentrations of 13 trace elements were determined in 1032 muscles of 54 small-scale fisheries species collected from the Seychelles waters between 2013 and 2019. Overall, profiles were dominated by zinc (Zn) > arsenic (As) > iron (Fe) > copper (Cu) > selenium (Se), with the spiny lobsters, spanner crab and octopus exhibiting the highest levels of As, Cu and Zn while fish had higher Fe concentrations. Both taxonomy-dependent processes and ecological factors explained the interspecific differences of trace element profiles observed. A benefit-risk assessment revealed that crustaceans and cephalopods were good sources of Cu and Zn. One portion of any fish could provide 30–100 % of daily Se needs, and one portion of demersal and pelagic teleost fish could bring 5–20 % of Cu, Fe and Zn needs, especially for young adult and adult women. Finally, our analysis showed that there was very low health risks associated with small-scale fisheries consumption for the Seychelles population. Highlights: Trace element concentrations were determined in 54 tropical fisheries species Teleosts and sharks had the highest Fe, Hg and Se concentrations Spiny lobsters and octopus had the highest As, Cu, and Zn concentrations Small-scale fisheries contributed significantly to the communities' daily mineral needs No to very low exposure risks to Ag, Cd, Hg and Pb were observed Diversification of species consumed would maximise benefits and limit risks for populations